Pendidikan Perdamaian Dengan 12 Nilai Dasar Perdamaian - Darmawan, I Putu Ayub (BIA, 2019)
Conflict is a problem that is being faced in Indonesia. A peaceful way is needed to bring peace to a multicultural nation. From the analysis of various biblical literature and texts there are several peace values, including education for peace must guide students to accept themselves, peace education provides guidance to avoid bad prejudice, needs to be built understanding and attitudes that respect ethnic diversity, religious differences, different types sex, social status such as poor wealth, and group differences, in an effort to build a path for peace, students need to understand diversity, understand conflict, build an attitude of resisting violence, willingness to start admitting mistakes, and willingness to forgive.Abstrak: Konflik merupakan masalah yang sedang dihadapi di Indonesia. Perlu dilakukan cara damai untuk menghadirkan perdamaian di bangsa yang multi-kultural.  Dari analisis berbagai literatur dan teks Alkitab ada beberapa nilai-nilai per-damaian, antara lain pendidikan untuk perdamaian harus membimbing murid menerima dirinya sendiri, pendidikan perdamaian memberikan bimbingan untuk mengindari prasangka buruk, perlu dibangun pengertian dan sikap yang meng-hargai keragaman etnis, perbedaan agama, perbedaan jenis kelamin, status sosial seperti kaya miskin, dan perbedaan kelompok, dalam upaya membangun jalan menunju perdamaian maka murid perlu memahami adanya keragaman, memahami konflik, membangun sikap menolak kekerasan, adanya kerelaan untuk memulai mengakui kesalahan, dan kerelaan untuk memberi maaf.